2010
DOI: 10.1111/j.1537-2995.2009.02413.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective monitoring of plasma and platelet transfusions in a large teaching hospital results in significant cost reduction

Abstract: Prospective triage and evidence-based transfusion practice education reduced unnecessary plasma and PLT transfusions and health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 18 publications
3
42
0
3
Order By: Relevance
“…Especialmente no Brasil e no âmbito do financiamento público do sistema de saúde, mecanismos dirigidos a esse objetivo podem se tornar cada vez mais importantes. (14,15,26) O estudo em questão foi capaz de mostrar que uma intervenção relativamente simples, como a informatização da prescrição do sangue e hemocomponentes, pode mudar de maneira significativa a prática transfusional de uma instituição.…”
Section: Discussionunclassified
“…Especialmente no Brasil e no âmbito do financiamento público do sistema de saúde, mecanismos dirigidos a esse objetivo podem se tornar cada vez mais importantes. (14,15,26) O estudo em questão foi capaz de mostrar que uma intervenção relativamente simples, como a informatização da prescrição do sangue e hemocomponentes, pode mudar de maneira significativa a prática transfusional de uma instituição.…”
Section: Discussionunclassified
“…1,9 Masih ditemukan banyak sekali variasi dalam hal indikasi transfusi baik pada trombosit maupun sel darah merah, untuk itu diperlukan penelitian prospektif tersamar untuk menghasilkan petunjuk berbasis bukti. 4,10,11 Pada studi kami terlihat kasus ITP mempunyai rasio kebutuhan tertinggi, yaitu setiap kasus terindikasi transfusi rata-rata memerlukan trombosit 14,7 unit. Hal ini memerlukan telaah lebih lanjut, salah satunya dengan mengevaluasi ulang riwayat indikasi dilakukannya tranfusi TC pada ITP kasus demi kasus.…”
Section: Pembahasanunclassified
“…Edukasi berbasis bukti akan sangat mengurangi transfusi TC dan menekan biaya perawatan. 11,12 Penyediaan produk untuk transfusi trombosit memerlukan sumber logistik yang baik dan mempertimbangkan faktor biaya. Kesulitan menjaga ketersediaan TC membutuhkan usaha untuk mencari banyak donor.…”
Section: Pembahasanunclassified
“…Marques et al [63] showed decreased RBC units and percentage of patients transfused through a combination of education and audits [63]. Sarode et al [65] was able to reduce inappropriate plasma usage by 60% and platelet usage by 25% after hospital wide education and prospective monitoring by laboratory staff and housestaff. While concurrent review of each product upon request can be successful, it is very labor intensive, difficult to sustain long-term, and can delay delivery of blood products.…”
Section: Educational Interventionsmentioning
confidence: 99%
“…Review strategies concurrent with physician ordering have been described for RBC [63] as well as for plasma and platelet products [62,64,65]. Marques et al [63] showed decreased RBC units and percentage of patients transfused through a combination of education and audits [63].…”
Section: Educational Interventionsmentioning
confidence: 99%